URGENSI FUNGSI MANAJEMEN “PLANNING” DALAM MANAJEMEN PENDIDIKAN ISLAM (Studi Kasus Pesantren Tahfizh Daarul Qurán) - Mansur, Jam'an Nurchotib; Tarmizi, Tarmizi (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2025)
Planning is the first point that is carried out in implementing the management function in the organization, both George R Terry with POAC, Henry Fayol with POCCC, John F. me with POMC, Luther M Gulick with POSDCRB, Harold Koots and Cyriil O. Donnel with POSDC and Stephen P. Robins and Timoty A. Judge with POLC, Edwards Deming with PDCA and John D. Millet with Directing and Facillitating. All management experts put planning in the first place. The ability of pesantren to survive until now in the midst of the rapid flow of globalization is due to the ability of pesantren to manage their institutions. The growth of Islamic educational institutions proves that Islamic educational institutions have experienced extraordinary development, marked by the great interest of the public to enroll their children in Islamic educational institutions. The ability of the Tahfizh Daarul Qurán Islamic Boarding School in developing management functions, namely. Planning is able to improve the quality of the institution's management. The research is field research, while the approach used is qualitative descriptive. Meanwhile, the data analysis procedure of this research is reduction, display, conclusion drawing. As for the technical data analysis using the Nvivo 12 Plus application. In general, the management function, namely Planning, runs in accordance with the vision and mission of the institution. Daarul Qur'an forms a Deputy work unit that functions to carry out planning, evaluation, monitoring and coaching activities. Planning is set at a national working meeting that sets and lays down the outline of the institution's policy.